Analisis Penerapan Metode Simpleks Linier Programming Pada Home Industry Martabak - Ayu Azizah; Rani; Khoirul Ulum; Faizal Roni; Eni Reptiningsih (Journal of Trends Economics and Accounting Research, 2023)
Linear programming is a planning technique that uses mathematical models with the aim of finding the best product combinations in preparing an allocation of limited resources in order to achieve goals that are used optimally Sofjan Assauri (Hermawan, 2016). The simplex method is an approach in solving linear programming problems that have two or more decision variables where determining the optimal combination is done through repeated iterations of the simplex table until the optimum value is found in the optimization problem which includes maximizing profits or minimizing costs. The martabak home industry is one of the businesses operating in the culinary sector. One of the problems faced by the Martabak 88 home industry is determining the optimum production amount so as to obtain maximum profits. Therefore, a method is needed to determine the right combination of products made and the combination of products produced. The simplex method is the method used in this research to estimate the maximum profit obtained from sweet martabak and egg martabak.